Advances in irrigation agronomy plantation crops - Carr, M. K. V. (Cambridge University Press, 2012)
Irrigation has been used for thousands of years to maximize the performance, efficiency and profitability of crops and it is a science that is constantly evolving. This potential for improved crop yields has never been more important as population levels and demand for food continue to grow. Recognising the need for a coherent and accessible review of international irrigation research, this book examines the factors influencing water productivity in individual crops. It focuses on nine key plantation/industrial crops on which millions of people in the tropics and subtropics depend for their livelihoods (banana, cocoa, coconut, coffee, oil palm, rubber, sisal, sugar cane and tea). Linking crop physiology, agronomy and irrigation practices, this is a valuable resource for planners, irrigation engineers, agronomists and producers concerned with the international need to improve water productivity in agriculture in the face of increased pressure on water resources